A cross‐cultural validation of the Resiliency Scale for Young Adults in Canada and China. Issue 2 (12th December 2018) - Wilson, Claire A.; Plouffe, Rachel A.; Saklofske, Donald H.; Yan, Gonggu; Nordstokke, David W.; Prince‐Embury, Sandra; Gao, Yan
Abstract: The current study reports on a cross‐cultural validation of the recently developed Resiliency Scale for Young Adults (RSYA) with two samples consisting of 617 Canadian university students and 651 Chinese university students. Confirmatory factor analysis, tests of cultural invariance, and correlations with relevant individual difference variables were conducted as tests of validity. In the Chinese sample, confirmatory factor analysis supported the factor structure of the RSYA and internal consistency reliabilities for the three factors and 10 facets were good‐to‐excellent. Cultural and gender invariance were supported. Correlations with depression, anxiety, stress, flourishing, and life satisfaction were also in the expected direction in the Chinese sample. These findings provide additional support for the RSYA as a reliable and valid measure of personal resiliency for Chinese young adults. Findings support the three‐factor model of personal resiliency in both Canadian and Chinese young adults, as well as cultural and gender invariance. The robustness of this model has implications for assessing and developing resiliency cross‐culturally.